Coastal Erosion Mitigation Based Community Empowerment Strategies in Jerowaru District of East Lombok Regency, West Nusa Tenggara Province, Indonesia - Ramadhan, Dewi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to analyze and formulate alternative form of coastal erosion mitigation by using AHP analysis (Analythical Hierarchy Process) and formulate empowerment strategies of coastal erosion response community in Jerowaru district of East Lombok Regency. This research was descriptive qualitative research which used observation, interview and documentation as intruments of data collection. Two types of data were used, namely primary data and secondary data. Data was analyzed by using AHP and SWOT. The result of this research found that there were 6 criteria of coastal erosion mitigation. They are: community empowerment (0,444), Mangrove trees Cultivation (0,234), settlement relocation (0,153), Environment control (0,85), Grid stone (0,53), government’s role (0,31). The strategy used to prevent the erosion was Grid stone installation in coastal erosion mitigation, a routine public counseling, improving community awareness of coastal area preservation, the relocation of community settlement which was affected by coastal erosion and preventing the development of settlements in the areas prone to coastal Erosion.